Examining Evidence for Passive in Yoruba - Balogun, Bunmi (Linguistics, 2022)
The construction of English passives is formed by placing the noun which denotes the subject of the action in the sentence to the object position and then making the object of the sentence dislocate to the subject position. Other transformations include the change of the auxiliary verb and the inflection of the main verb. The focus of this study however is on Yoruba passives, a topic that is very passive in the Yoruba grammar literature. The study's primary aim then is to investigate the passives in Yoruba. No study to the best of my knowledge has lay claim of the existence of passives in Yoruba, a Kwa language under the Niger-Congo language family which is spoken mostly in the Western part of Nigeria. This study provides evidence to argue for the existence of (forms of) passives in the language. In the realization of Yoruba passives, the subject in the active verb is physically dislocated to become an agent phrase of the passive sentence or deleted. However, the object's position in particular differs strikingly from the English passive as the object of the active verb does not move to the subject position. The pronoun a occupies the subject position, and it is in [Spec, TP] as the object makes no movement. In Yoruba, the auxiliary of the passive is not a consistent form in that auxiliaries change based on the sentence they are used in. Similarly, the Yoruba verbs are not morphologically inflected. Hence, the verb of the active sentence retains its form in the passive. I speculate that object DP cannot fulfil the requirement of T's EPP, hence its inability to move. The analysis of the study will be done in comparison to English passive constructions and selected languages that have peculiar cases of passives and analyses will be represented in tree diagrams. The paper is cast within the Minimalist Program of syntax.